+0

# I have 2 questions

0
294
1

1. Some functions that aren't invertible can be made invertible by restricting their domains. For example, the function $$x^2$$ is invertible if we restrict $$x$$ to the interval $$[0,\infty)$$, or to any subset of that interval. In that case, the inverse function is $$\sqrt x$$. (We could also restrict $$x^2$$ to the domain $$(-\infty,0]$$, in which case the inverse function would be $$-\sqrt{x}$$.)

Similarly, by restricting the domain of the function $$f(x) = 2x^2-4x-5$$ to an interval, we can make it invertible. What is the largest such interval that includes the point $$x=0$$?

2. The function $$f(x) = \frac{cx}{2x+3}$$
satisfies $$f(f(x))=x$$, $$x\ne -\frac 32$$ for all real numbers . Find $$c$$.

Guest Jun 20, 2017
Sort:

### 1+0 Answers

#1
+80874
+1

1.  The vertex of this parabola is (1, -7)....so.....restricting the domain to  (-infinity, 1 ] will  make the function invertible...... and  x  = 0  lies within this interval

2. If f ( f(x) )  = x        we can write

c ( (cx) / [2x + 3] )

________________        =  x   multiply  throgh by the denominator on the left side

2 ( (cx/ [2x + 3]) + 3

c( (cx)) / [2x + 3] )  = x  [ 2 ( (cx) / [2x +  3] ) + 3]     simplify

c^2x / [2x + 3]  =  x [ 2cx + 6x + 9 ] / [2x + 3]

c^2x  =  2cx^2 + 6x^2  + 9x

2cx^2 + 6x^2 + (9 - c^2) x  = 0

Note....that for any x, this will equal 0 whenever

2c +  6 + (9-c^2)  = 0

-c^2  + 2c + 15  = 0     multiply through by -1

c^2  -  2c  - 15  = 0  factor

(c - 5) (c + 3)  = 0

So....setting each factor to 0 and  solving for c we have the possible values c = 5  or c = -3

Test c = 5  in  f(f(x))

5[5x /[2x + 3] ]                         [  25x ] / [2x + 3]

_______________     =        _________________  =   25x  /  [ 16x + 9 ]

2 [ 5x / [2x + 3]] + 3             [10x + 6x + 9]/ [2x + 3]

So  c = 5  is not a solution

Test  c  = -3  in  f (f (x))

-3 [ -3x / [2x + 3] ]                  [ 9x] / [2x + 3]                        9x

________________     =     __________________   =      ___     =    x

2 [ -3x / [2x + 3] ] + 3           [-6x + 6x + 9] / [2x + 3]             9

So....  c  =  -3

CPhill  Jun 20, 2017

### 16 Online Users

We use cookies to personalise content and ads, to provide social media features and to analyse our traffic. We also share information about your use of our site with our social media, advertising and analytics partners.  See details